Resistance to Mate Guarding Scale in Women: Psychometric Properties - Alita J. Cousins; Madeleine A. Fugère; Matthew L. Riggs (Evolutionary Psychology, 2015)
One individual's actions may affect the evolutionary fitness of another individual. Sexually antagonistic coevolution occurs when one partner's behavior decreases the fitness of the other partner ( Rice, 1996 ). This conflict pressures the other partner to counter these disadvantageous actions. Mate guarding is a mate retention tactic aimed at keeping a partner from cheating. Mate guarding may reduce mate choice, especially for extra pair mates. Therefore, some individuals may resist their partner's mate guarding tactics. We developed a scale to measure resistance to mate guarding and tested it in women ( N = 1069). Using exploratory factor analysis (EFA), six theoretically sound factors emerged and explained 69% of the variance. Confirmatory Factor Analysis showed strong support for the six original subscales as well as for the overall scale. The subscales had high reliability. The validity of the Resistance to Mate Guarding Scale was also excellent. Women who stated they used more resistance to mate guarding strategies also indicated that they had partners who mate guarded more, were less invested in their relationships, felt their partners were more controlling, had a more avoidant attachment style, and had a more unrestricted sociosexual orientation.